Conceptual changes for and during working life - Henny P.A. Boshuizen; Stella Vosniadou; Erno Lehtinen (Pergamon Press., 2022)
Rapid and radical changes in science, technology and society may result in new scientific concepts and new workplace practices, which require fundamental restructuring of prior knowledge. Over the years a noteworthy body of research has documented the processes of conceptual change, the learning mechanisms involved, and the instructional methods and strategies that can promote conceptual changes. This research, however, focused young learners in school settings. Conceptual changes in working life go beyond traditional conceptual change consisting of processes and mechanisms that involve the interaction between expertise development and workplace learning processes.This Special Issue investigates whether and how conceptual change research can be extended from learning in schools to learning in professional life.